Stained glass painting during the second half of the 20th century in Latvia, its tendency development in nowadays - Groza, Vineta (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
Stained glass painting during the second half of the 20th century in Latvia, its tendency development in nowadays. The stained glass panel ranks among the most interesting fields of monumental decorative art. In Soviet glass art history Latvian stained glass artists occupy the foremost places in this technique. The classical stained glass technique was combined with painting and sandblasting elements, which were incorporated into geometric monumental compositions. Latvian stained glass artists still followed classical stained glass traditions. The use of painting on glass declined. The dynamism of the composition was achieved through lead calm line rhythms. The other innovation in Latvian stained glass was introduced by many glass artists who used float glass in their stained glass panels in the middle of the 1960s. The first Latvian stained glass exhibition was held in 1971 and represented new glass technical perfection and creative imagination with the works of Latvian stained glass artists. In various publications, books, magazines and newspapers in Latvia, statements may be found on the theory of arts and significance of decorative art. In this area, surveys on development of glass painting in Latvia have been made by T. Grasis and I. Audere. Area of stained glass painting has not been sufficiently explored and systemized. The purpose and the task of this paper shall be preparing of a historical review on trends in the development of stained glass painting in the area of decorative arts in Latvia during the second half of 20th century and nowadays. Analysis of visual expression of the stained glass from the perspective of monumental painting. To explore contribution and significance of stained glass artists of the enterprise Māksla (1945) in the development of the area of stained glass painting. To assess tuition methods in the Department of Glass Arts of the Art Academy in the context of development of the Latvian decorative arts (stained glass painting). Methods of the paper are cultural, comparative and structural. The outcomes of the paper actualize significance of the glass painting from the perspective of modern arts.